The Post-Quantum Cryptography Challenge: A Security Analysis of Lattice-Based vs. Code-Based Algorithms - Loso Judijanto; Zhou Hui; Sun Wei (Yayasan Adra Karima Hubbi, 2026)
The emergence of large-scale quantum computers poses a critical threat to classical public-key cryptographic systems, prompting the rapid development of post-quantum cryptography as a foundational component of future digital security. Lattice-based and code-based algorithms have become leading candidates due to their strong conjectured resistance to quantum attacks; however, their comparative security characteristics remain insufficiently examined under unified analytical frameworks. This study aims to provide a comprehensive security analysis of lattice-based and code-based post-quantum cryptographic algorithms by evaluating their resilience against known classical and quantum attack vectors. A structured methodological approach is employed, combining complexity-theoretic assessment, parameter-sensitivity evaluation, and simulated attack modeling across representative schemes such as CRYSTALS-Kyber, NTRU, Classic McEliece, and BIKE. The results indicate that lattice-based schemes offer strong security margins under current attack models but exhibit notable sensitivity to parameter misconfiguration and structured lattice weaknesses. Code-based schemes demonstrate exceptional robustness due to the hardness of decoding random linear codes, yet face practical limitations in key size and implementation overhead. The study concludes that both families remain viable for post-quantum standardization, although their security assurances depend heavily on careful parameter selection and continued cryptanalytic scrutiny as quantum hardware evolves.